Crystalline structure and polymorphism in powders and thin films of dibenzotetraaza[14]annulene - Udovitskiy, V.G. (Журнал физики и инженерии поверхности, 2016)
The increasing interest in dibenzotetraaza[14]annulene (TAA) is motivated by the demonstrated perspectives for using this organic semiconductor in actively progressive now spintronics and in other fields of electronics. This work is the first study on polymorphism, which may occur in powder and in thin TAA films. The results of this study showed that the initial TAA powder synthesized by chemical methods are both now known polymorphic forms of TAA which were registered at Cambridge Crystallographic Data Centre as GAGVAL and GAGVAL01. It was also found that at the condensation of thin films G-form initially formed while after increasing the film thickness the G01-form will forms also and a continuous films have twophases and contain both known polymorphs — G and G01. The X-ray diffraction pattern indicated also that crystallites in thin TAA films show a strong preffered orientation (texture) with the (100) plane (for G-polymorph) and (002) plane (for G01-polymorph) parallel to the surface of the substrate